Thermal Safety and Efficiency of a 24 Volt DC Motor Used as a Prime Mover for a Single-Phase Generator - Sri Agustina; M. Aldi Ramadhan; Herlina; Wirawan Adipradana (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
Brushed DC motors are often used as low-cost prime movers in small generator sets. However, users rarely evaluate thermal safety together with efficiency when the set operates under repeated electrical loads. This study investigates a 24 V, 750 W brushed DC motor mechanically coupled to a 220 V, 50 Hz single-phase synchronous generator and a lamp-based resistive load bank. Three generator load levels were tested (1000 W, 1400 W, and 2600 W). Each test ran for 10 minutes to represent a short-time duty that is practical for repeated laboratory trials and long enough to reveal a clear temperature trend while maintaining safe operation. The DC terminal voltage (V), input current (A), and motor surface temperature (°C) were recorded every 2 minutes. Input power, temperature rise, estimated loss power, output power, and apparent efficiency were then computed at the 10-minute mark. The results show a monotonic temperature rise with load: after 10 minutes, the motor surface temperature reached about 36.0°C (1000 W), 39.3°C (1400 W), and 41.5°C (2600 W), corresponding to a 9–15 K rise above ambient. The apparent efficiency remained high at 94.3–96.3%. These findings support a simple and replicable approach to discussing the thermal safety and efficiency of small motor–generator sets in laboratory practice.